2022
DOI: 10.3390/app122211568
|View full text |Cite
|
Sign up to set email alerts
|

Dust Dispersion Characteristics of Open Stockpiles and the Scale of Dust Suppression Shed

Abstract: The storage of bulk materials in open yards can easily lead to contamination in the form of suspended particles. The creation of enclosed spaces for open yards is an effective measure to stop the dispersion of dust to the outside. In this study, a reliable numerical model was developed to calculate the impact range of dust dispersion using the concentration–velocity distribution of pollutants based on the DPM-CFD simulation, and validated by field measurement data. Then, the hazard distance was defined as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The results showed that the porous fence and barrier had a positive effect on reducing the local rate and reducing the dust erosion rate, that the actual accumulation geometry with adjacent structures would affect the wind velocity distribution, that the inlet angle was a key factor affecting the effectiveness of solid and porous wind barriers, and that the placement of porous barriers between the stockpiles could effectively reduce dust emissions. Ma et al [13,14] used theoretical methods and numerical simulations to investigate the extent of dust pollution in open dumps and to determine the size of dust barriers. Using DPM-CFD simulations and field measurements, the dispersion characteristics of dust in open yards were determined.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the porous fence and barrier had a positive effect on reducing the local rate and reducing the dust erosion rate, that the actual accumulation geometry with adjacent structures would affect the wind velocity distribution, that the inlet angle was a key factor affecting the effectiveness of solid and porous wind barriers, and that the placement of porous barriers between the stockpiles could effectively reduce dust emissions. Ma et al [13,14] used theoretical methods and numerical simulations to investigate the extent of dust pollution in open dumps and to determine the size of dust barriers. Using DPM-CFD simulations and field measurements, the dispersion characteristics of dust in open yards were determined.…”
Section: Introductionmentioning
confidence: 99%
“…Weiwu Ma et al [13] developed a field-validated model that analyzes the dust dispersion effects of open stockpiles using CFD. Additionally, the closed warehouse structure was comprehensively analyzed and validated for warehouse construction using CFD.…”
Section: Introduction Of Latest Technologies and Researchmentioning
confidence: 99%